"La declaración judicial de paternidad y de la maternidad y su incidencia en la integración del núcleo familiar" - Ramos Gaibor, Paulo César (2013)
This legal research, the theme JUDICIAL DECLARATION OF PATERNITY AND MATERNITY AND ITS IMPACT ON THE INTEGRATION OF HOUSEHOLD, aimed generally determine that the regulatory domain of the judicial declaration of paternity and maternity ensure constitutional right of children to enjoy the care and protection of their parents. For this purpose, we analyzed the legal standard governing the declaration of parenthood contained in Articles 253, 254 and 258 of the Ecuadorian Civil Code for the respective proposal submission. The framework contains thematic aspects of the two variables of the hypothesis, which is based conceptual framework relevant. It analyzed the legal standard governing judicial declaration of paternity and maternity, the same that restrict the content of the constitutional rights of the children, so that the results and information from the field investigation, determined the existence of such legal inconsistencies in those articles of the Civil Code, and the need to reform. Mentioned that legal rules violate the principle of the best interests of the child to dismiss the paternity suit if it proves the blatant misconduct of the mother during the legal period of conception. As for legal reform proposal, it presents a brief background, rationale and objectives. In developing the proposed reform of the Arts. 253, 254 and 258 of the Civil Code makes a statement of reasons and the proposal is based legally in the recitals